China’s Hybrid Response towards Emerging Security Alliances in the Indo-Pacific: A Defense Diplomacy Perspective - Andriyanto, Kristoforus Evan; Pedrason, Rodon; Perwita, Anak Agung Banyu; Surjaatmadja, Surachman (CV. Rayyan Dwi Bharata, 2025)
The intensifying geopolitical rivalry in the Indo-Pacific has made China employ a hybrid strategy to respond to emerging security alliances in the Indo-Pacific, such as the QUAD, AUKUS, JAPHUS, and SQUAD, by combining militarization, economic coercion, and selective diplomatic engagement, to resist perceived containment while avoiding direct conflict. This qualitative research aims to assess the effectiveness of the strategies and analyze the impact of the responses on regional security stability, through the lens of defense diplomacy and hybrid warfare theoretical framework. Rooted in realist principles, China's response complicates the effectiveness of alliance-based security frameworks and undermines traditional defense diplomacy norms. While China's assertive actions heighten regional tensions, its simultaneous engagement in bilateral economic deals and crisis management mechanisms offers temporary de-escalation. China's strategic maneuvers are designed to solidify its long-term hegemony and test the resilience of regional security frameworks while diminishing US influence.